Cross-cultural Ezra Pound - Gery, John 1953-; Baumann, Walter 1935-; McKnight, David 1952- (Clemson University Press, 2021)
"This volume offers new interpretations of Pound's poetics, as well as new perspectives on his critical reception globally. It covers Pound's work from his beginnings as a young poet in Philadelphia in the first decade of the century through his most productive years as a poet, critic, and translator to the first critical treatments of his work in the 1940s and 50s, and on to translations of The Cantos spanning the last fifty years." (Verlagsinformation)
Includes bibliographical references and index
Keywords: Pound, Ezra -- 1885-1972 -- The cantos; Lyrik; Übersetzung; Interkulturalität; Pound, Ezra / 1885-1972 / Criticism and interpretation; Pound, Ezra / 1885-1972 / Public opinion